2008
DOI: 10.3855/jidc.278
|View full text |Cite
|
Sign up to set email alerts
|

Viral gastroenteritis and diversity of rotavirus strains in Colombian children: a systematic review

Abstract: Background: To determine the epidemiological profile of viruses associated with acute gastroenteritis in children younger than 5 years of age and the distribution of rotavirus genotypes circulating in Colombia. Methodology: We conducted a review of 23 studies published in Spanish and English, plus an analysis of the detection rates of rotavirus as well as other viruses associated with acute gastroenteritis in young children from 1984 to 2006 in the three Colombian regions. This review also included the only tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…From 2008 to 2010, epidemiological study of adenovirus diarrhea in Borazjan, Bushehr Province, Iran, showed a prevalence rate of 5.1% in children less than seven years of age with acute gastroenteritis. This result is comparable to the disease burden of adenovirus reported in other investigates in Iran and different countries which was shown to be responsible for 1.35 to 10.4% of all cases of gastroenteritis (Jarecki et al, 1993;Modarres et al, 2006;Ospino et al, 2008;Kamel et al, 2009;Hamkar et al, 2010;Moyo et al, 2011;Zhang et al, 2011). We detected a relatively high rate of enteric adenovirus among infants and young children less than 2 years of age, which is in agreement with previous reports in Thailand (Herrmann et al, 1988), Iran (Modarres et al, 2006), Bangladesh (Dey et al, 2009a), Turkey ( Ozdemir et al, 2010) and India (Dey et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…From 2008 to 2010, epidemiological study of adenovirus diarrhea in Borazjan, Bushehr Province, Iran, showed a prevalence rate of 5.1% in children less than seven years of age with acute gastroenteritis. This result is comparable to the disease burden of adenovirus reported in other investigates in Iran and different countries which was shown to be responsible for 1.35 to 10.4% of all cases of gastroenteritis (Jarecki et al, 1993;Modarres et al, 2006;Ospino et al, 2008;Kamel et al, 2009;Hamkar et al, 2010;Moyo et al, 2011;Zhang et al, 2011). We detected a relatively high rate of enteric adenovirus among infants and young children less than 2 years of age, which is in agreement with previous reports in Thailand (Herrmann et al, 1988), Iran (Modarres et al, 2006), Bangladesh (Dey et al, 2009a), Turkey ( Ozdemir et al, 2010) and India (Dey et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…(Jarecki et al, 1993;Aminu et al, 2007;Kargar et al, 2011b;Rimoldi et al, 2011). Studies conducted in different regions of the world have indicated that enteric adenoviruses are responsible for 1.35 to 10.4% of the cases of acute gastroenteritis among infants and children <5 years of age (Ospino et al, 2008;Kamel et al, 2009;Simpore et al, 2009;Moyo et al, 2011;Zhang et al, 2011). In Iran, very little data on illness caused by adenovirus has been collected.…”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus was isolated from 3.1% of cases. In some previous studies around the world, rotavirus was found as one of the most frequently detected enteropathogens, with high isolation rate as in Gaza, Tunisia, Saudi Arabia, Jordan, Europe and South America [1] , [10] , [18] , [30] - [34] . These differences could be explained by the difference of the age groups that were investigated in each study and also the laboratory methods used such as ELISA or PCR techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus was isolated from 3.1% of cases. In some previous studies around the world, rotavirus has been found to be one of the most frequent enteropathogens, with high detection rates reported from Gaza, Tunisia, Saudi Arabia, Jordan, Europe and South America [1,10,18,[30][31][32][33][34]. These differences could be explained by differences in age groups investigated in each study, by laboratory methods, and seasonality.…”
Section: Discussionmentioning
confidence: 94%